Effect of temperature and ouabain on th Na+--K+ activated membrane ATPase and electrogenic ionic pump of the golden hamster and mouse diaphragm - Dlouhá, H; Donselaar, Y; Teisinger, J; Vyskocil, F (Physiologia Bohemoslovaca, 1980)
The activity of membrane Na+--K+-ATPase and electrogenic ionic pump was estimated by biochemical and electrophysiological techniques on diaphragm muscles of mouse and non-hibernating golden hamster between 5 degrees C to 37 degrees C. The electrogenic capacity of ionic pump (measured as maximum hyperpolarization after adding 5 nmol/l K+ to Na+-enriched muscle) was highest at 37 degrees C for the mouse and between 25--30 degrees C for the golden hamster. At lower temperatures (15 degrees C--5 degrees C), the hyperpolarization after adding K+ reversed to depolarization between 15 degrees C and 10 degrees C in the case of the mouse. In the hamster, the slight hyperpolarization persisted even at 5 degrees C. With decreasing temperature, the activity of membrane ATPase of mouse and hamster membrane fraction decreased in both cases to the same extent between 37--25 degrees C. Within the temperature range between 10 degrees C and 5 degrees C the activity of this enzyme of hamster preparations was about 2.4 times higher than in the case of the mouse. In the mouse Na+-enriched diaphragm, ouabain (10(-4) mol/l) decreased the resting membrane potential (RMP) in a K+-free solution at 20 degrees C by about 5 mV, but in the golden hamster preparation, ouabain in the same concentration increased RMP of Na+-enriched diaphragm fibres by more than 5 mV. The activity of membrane ATPase of hamsters was increased by 10(-4) mol/l ouabain more than 2.5 times in a K+-free reaction medium, whereas in the case of the mouse no change of enzyme activity was observed. This indicates that ouabain can be substituted for potassium as an activator of membrane ATPase in the sarcolemma of golden hamster muscle fibres.
Keywords: Potassium; bránice; křečci praví; draslík; Cell Membrane; křeček rodu Mesocricetus; Mice; sodíko-draslíková ATPasa; Muscles; ouabain; Ouabain; Mesocricetus; ženské pohlaví; zvířata; Temperature; svaly; buněčná membrána; myši; sodík; Diaphragm; Cricetinae; Sodium-Potassium-Exchanging ATPase; Female; Sodium; teplota; Animals